Fenomenologi Ta’aruf dan Menikah Muda di Pengajian Islamic Centre Purwakarta - Yulianti; Nabila Noerfadjria (Jurnal Komunikasi Islam, 2022)
The most common factor to divorce is communication problems. Self-disclosure interactions between couples have become the most vital thing for building closeness within them. This study aims to understand the motives and meaning of ta'aruf for women who decide to get married at a young age in Islamic Center Congregation Purwakarta. By using a qualitative research approach, the findings indicate that ta'aruf is a part of the self-disclosure needed within couples' relationships. In regard to the motives for getting married at a young age, they are because of religious reasons, a sense of uncertainty arising from past relationships, and to gain the pleasure of their parents (because motive). In addition, it is also because of the desire to achieve goals and maintain dignity and self-purity (in order to motive). While the construction of meaning from the ta'aruf is as a form of the actualisation of faith to Allah Swt., the media to gain the pleasure of Allah Swt., and the fulfilment of psychological needs as well.